Mobile phone technology in the management of asthma. - Ryan, D; Cobern, W; Wheeler, J; Price, D; Tarassenko, L (2005)
Peak flow monitoring is widely recommended as part of a self-management plan for asthma. We conducted an observational study using electronic peak flow monitoring and mobile phone technology in a UK general practice population over a nine-month period. Patients between 12 and 55 years of age who required treatment with regular inhaled steroids and (as needed) bronchodilators were recruited from nine general practices. Patients were included if their asthma was considered stable (i.e. no exacerbation in the previous three months). No therapeutic intervention was proposed. The primary outcome measure was compliance. In all, 69% of the 46 participants who filled in the post-study questionnaire were 'satisfied' or 'very satisfied' by the study, citing the ease of use and the increased autonomy and understanding of asthma as the main advantages. In total, 74% indicated that the system had helped to improve their ability to manage their symptoms. The most positive features of the telemedicine system were described as follows: increased awareness and information about asthma, improved ability to monitor/manage the condition with the feedback screens on the mobile phone and ease of use.